2007
DOI: 10.21314/jrmv.2007.007
|View full text |Cite
|
Sign up to set email alerts
|

Backtesting VaR models:a two-stage procedure

Abstract: Academics and practitioners have extensively studied Value-at-Risk (VaR) to propose a unique risk management technique that generates accurate VaR estimations for long and short trading positions. However, they have not succeeded yet as the developed testing frameworks have not been widely accepted. A two-stage backtesting procedure is proposed in order a model that not only forecasts VaR but also predicts the loss beyond VaR to be selected. Numerous conditional volatility models that capture the main charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A GARCH(1,1) specification has been selected as it has been shown that a lag of order 1 on the squared residuals and the conditional variance are sufficient to model conditional volatility (Angelidis and Degiannakis, 2007;Hansen and Lunde, 2005).…”
Section: Garch and Figarch Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…A GARCH(1,1) specification has been selected as it has been shown that a lag of order 1 on the squared residuals and the conditional variance are sufficient to model conditional volatility (Angelidis and Degiannakis, 2007;Hansen and Lunde, 2005).…”
Section: Garch and Figarch Modellingmentioning
confidence: 99%
“…However, the proposed specification allows for discontinuous or non-synchronous trading in the stocks making up an index (see Angelidis and Degiannakis, 2007;Lo and MacKinlay, 1990). 9 The normal density function has been selected to reduce the degree of parameterisation of the model, in order to focus the analysis on the distinction between the long memory and short memory specifications for the conditional variance.…”
Section: Garch and Figarch Modellingmentioning
confidence: 99%
See 3 more Smart Citations